Revisiting Rosinante: reinterpretations of the cervantine character in Rosinante to the road again, Monsignor Quixote, and Travels with Charley - Marín Ruiz, Ricardo (Epos : Revista de filología, 2015)
Este artículo analiza la imagen que de Rocinante ofrecen tres autores claves en la Literatura Inglesa y Norteamericana del siglo xx, como son John Dos Passos, Graham Greene y John Steinbeck, quienes se aproximan a la figura de este célebre rocín desde diferentes perspectivas, como así se puede comporbar en sus novelas Rosinante to the Road Again (1922), Monsignor Quixote (1982), and Travels with Charley (1962) respectivamente. Previa al análisis de estas tres interpretaciones, la primera parte del artículo aborda algunas de las características que Cervantes confirió a su personaje, tales como su endeblez y su dimensión simbólica, rasgo este último que lo convierte en el único animal que posee la condición de personaje en Don Quijote. Una vez abordadas estas facetas de Rocinante, en la segunda parte se analiza hasta qué punto los autores seleccionados se ciñen a la concepción original del personaje cervantino y en qué medida lo convierten en objeto de una reinterpretación personal que, a menudo, se corresponde con una crítica de diversos aspectos —políticos, económicos, sociales— de la sociedad occidental actual . This article examines the image of Rosinante given by three of the most relevant writers in the English and American Literature from the 20th century: John Dos Passos, Graham Greene, and John Steinbeck, who approach the figure of this widely-known steed from different perspectives in Rosinante to the Road Again (1922), Monsignor Quixote (1982), and Travels with Charley (1962) respectively. Before undertaking the study of these three interpretations, the first part of the essay deals with some of the features Cervantes conferred on this endearing figure, such as his feebleness and the symbolic dimension which provides Rosinante with the condition of being the only animal having the status of character in Don Quixote. Once these features have been shown, the second part focuses on to what extent the three authors stick to the original conception of Rosinante, and to what extent make personal reinterpretations of this character which often correspond to a critic of different aspects —political, social, economic— of the Western society.